INTERTEXTUALITYOFTHEPERSONOSPHEREASAFACTOROFMETA-GENRE(CLIFFORDSIMAK“SHAKESPEARE’SPLANET”) - Паранюк, Дан; Тичініна, Альона (Чернівецький нац. Ун-т, 2023)
Thearticleunderstudiesdealswiththeissueofregenerationofgenreforms ofsciencefictionliteraturethrough its evolution. In the context of topical issues of poetics, it outlines the genrological status of science fiction and fantasy in terms of genre modifications –genre, genre variety, sub-genre, mega-genre, and meta-genre. Particular emphasis has been placed on the fact that the evolution of science fiction into a meta-genre format is due to a number of factors, such as the simulative nature of the chronotope of possible and parallel worlds, the change in the anthropological vector of texts, and the involvement of samples of other art forms (intermedial components). Inaddition, the activation of intertextual narratives in the personosphere (which becomes an important parameter of the meta-genre) has been identified as a marker of the genre evolution of fantasy. The creative activity of the American classic of science fiction prose CliffordSimak (1904–1988) may be regarded as a typical example of how science fiction writers appeal to “other authors’ texts”. This research relies on the analysis of his novel “Shakespeare’s Planet” (1976), in whichthe reader’s attention is mainly focused on the intertextual parameters of the personosphere, which significantly expands the hyper-real chronotope of the science fiction world. The works by William Shakespeare are identified as the prototexts for fantasy texts. Interpreted by Simak, the Shakespearean imagological narratives are implemented through quotations, reminiscences, anthropological allusions (the use of Shakespeare’s characters’ names), as well as through the introduction of the figure of Shakespeare himself into the fantasy personosphere. What is more, the figure of the English classic occasionally appears as the very center of the personosphere, its confocal axis. It has been determined in the article that the mystified and ironic story of Shakespeare’s timeless existence ferments the internal contentof the fantasy text. Besides, the personosphere of a fantasy novel with several fictional narratives also includes the classic’s texts, such as “Hamlet”, “Twelfth Night”, “The End Praises the End”, “The Comedy of Errors”, “King Lear”, “Macbeth”, “Othello”, “Pericles”, “The Taming of the Shrew”, “Richard III”, and “Titus Andronicus”. In this case, in Simak’s “Shakespeare’s Planet”, they perform the function of additional (implicit) narratives, and, consequently, as a particular (intertextual) link in the personosphere. In conclusion, the article claims that the consistent generation of new literary genre formats in the field of the cultural continuum is an immanent feature of the complex literary process, which can be fully realized only with the help of thereader’s rich receptive background
Keywords: poetics; meta-genre; genre; novel; personosphere;narrative;CliffordSimak;WilliamShakespeare.